Covid-19 Delta variant resulting in multi system thromboembolic disease - Gabriella Fluss; Victoria Cranwell; Ajit Rao; Joon Sub Lee; Ramy Elshafey; Marc Wallack; David Finlay (Annals of Vascular Surgery - Brief Reports and Innovations, 2022)
Infection with severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2/Covid-19) has been correlated with micro and macrovascular thrombosis. Reports have discussed localized thrombosis leading to ischemia, we report a case of diffuse systemic thromboembolism resulting in limb ischemia and organ damage from Covid-19 despite prompt anticoagulation. A 60-year-old unvaccinated male with a history of asthma, diabetes mellitus and coronary artery disease, presented with shortness of breath and right lower extremity pain. The patient was found to be Covid-19 Delta variant positive. CTA and transthoracic echocardiogram showed diffuse thromboembolic disease affecting the left ventricle, right kidney and bilateral lower extremities.